Usage of Local Fuel for Combined Generation of Thermal and Electric Power - G. I. Zhihar (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper reveals that it is necessary to ensure interaction of the various concerned ministries and institutions involved in storage and transportation of local fuel in order to increase its portion in the power balance of Belarus. Nowadays there is a problem to determine the most efficient and reliable designs of electric power plants for usage of local fuel while executing a combined generation of thermal and electric power on a large scale in respect of Belarus